Action Experience Changes Attention to Kinematic Cues - Filippi, Courtney A.; Woodward, Amanda L. (Frontiers in Psychology, 2016)
The current study used remote corneal reflection eye-tracking to examine the relationship between motor experience and action anticipation in 13-month-old infants. To measure online anticipation of actions infants watched videos where the actor’s hand provided kinematic information (in its orientation) about the type of object that the actor was going to reach for. The actor’s hand orientation either matched the orientation of a rod (congruent cue) or did not match the orientation of the rod (incongruent cue). To examine relations between motor experience and action anticipation, we used a 2 (reach first vs. observe first) x 2 (congruent kinematic cue vs. incongruent kinematic cue) between-subjects design. We show that 13-month-old infants in the observe first condition spontaneously generate rapid online visual predictions to congruent hand orientation cues and do not visually anticipate when presented incongruent cues. We further demonstrate that the speed that these infants generate predictions to congruent motor cues is correlated with their own ability to pre-shape their hands. Finally, we demonstrate that following reaching experience, infants generate rapid predictions to both congruent and incongruent hand shape cues—suggesting that short-term experience changes attention to kinematics.